Gradients of disturbance and environmental conditions shape coral community structure for south‐eastern Indian Ocean reefs. Issue 5 (23rd January 2018) - Zinke, Jens; Gilmour, James P.; Fisher, Rebecca; Puotinen, Marji; Maina, Joseph; Darling, Emily; Stat, Michael; Richards, Zoe T.; McClanahan, Timothy R.; Beger, Maria; Moore, Cordelia; Graham, Nicholas A. J.; et al.
Abstract: Aim: To describe, model and assess the relative importance of environmental and climatic factors likely influencing the regional distribution of coral cover and assemblages with contrasting life histories and susceptibilities to bleaching. Location: We compiled the first comprehensive empirical dataset for coral communities in the south‐eastern Indian Ocean (SEIO), incorporating information from 392 sites along the western coast of Australia and offshore atolls/islands across ~19° of latitude. Methods: We assessed hard coral cover and community composition to genus using point‐intercept transects or point‐count analysis of digital images taken along transects. We explored spatial variation in environmental conditions and in composition of corals with contrasting life histories. After de‐trending the temporal patterns, we assessed the relative importance of environmental metrics to coral cover, life histories and bleaching susceptibility using a full subsets model‐selection approach with generalized additive mixed models, accounting for both temporal and among site variation. Results: The distribution of temperature, light, the frequency of temperature anomalies and tropical cyclones appear to be drivers of coral community structure. Functional diversity of low‐ to mid‐latitude coral communities may convey some resilience to thermal stress, while higher latitude communities dominated by Competitive and Bleaching‐Susceptible taxa may lack this functional resilience. These patterns likely reflect varying historical exposure to cyclones and temperature anomalies. Main conclusions: As evident in recent years, changing background conditions and regimes of disturbance in coming decades will shift the distribution, functional diversity and resilience of coral reefs throughout the SEIO. The rate and magnitude of environmental change will ultimately determine the future of the tropical reefs and whether the higher latitude reefs provide some refuge from climate change. Our study highlights the need to quantify the distributional properties of key environmental metrics to better understand and predict reef condition through coming decades.